Default Premium - Catao, Luis (IMF Working Papers; Working Paper ;, 2015)
We re-assess the view that sovereigns with a history of default are charged only a small and/or short-lived premium on the interest rate warranted by observed fundamentals. Our reassessment uses a metric of such a 'default premium' (DP) that is consistent with asymmetric information models and nests previous metrics, and applies it to a much broader dataset relative to earlier studies. We find a sizeable and persistent DP: in 1870-1938, it averaged 250 bps upon market re-entry, tapering to around 150 bps five years out; in 1970- 2011 the respective estimates are about 400 and 200 bps. We also find that: (i) these estimates are robust to many controls including on actual haircuts; (ii) the DP accounts for as much as 60% of the sovereign spread within five years of market re-entry; (iii) the DP rises with market exclusion spells. These findings help reconnect theory and evidence on why sovereign defaults are infrequent and earlier debt settlements are desirable.